Synthesis and evaluation of peptidic thrombin inhibitors bearing acid-stable sulfotyrosine analogues. Issue 83 (1st October 2021) - Dowman, Luke J.; Agten, Stijn M.; Ripoll-Rozada, Jorge; Calisto, Bárbara M.; Pereira, Pedro José Barbosa; Payne, Richard J.
Abstract : We describe the incorporation of two acid-stable mimics of sulfotyrosine into thrombin-inhibiting peptides and assess their activity and binding mode. Abstract : Tyrosine sulfation is an important post-translational modification of peptides and proteins which underpins and modulates many protein–protein interactions. In order to overcome the inherent instability of the native modification, we report the synthesis of two sulfonate analogues and their incorporation into two thrombin-inhibiting sulfopeptides. The effective mimicry of these sulfonate analogues for native sulfotyrosine was validated in the context of their thrombin inhibitory activity and binding mode, as determined by X-ray crystallography.